Bibliometric study of immunotherapy for hepatocellular carcinoma - Li, Zhiyi; Zhang, Ying; Zhang, Baipan; Guo, Rui; He, Minhua; Liu, Zi-Ling; Yang, Lei; Wang, Hong (Frontiers in Immunology, 2023)
Background: Hepatocellular carcinoma (HCC) is a major global health concern, particularly given its late-stage diagnosis in many patients. Despite significant strides in chemotherapy and targeted therapy, drug resistance and issues like compromised post-treatment quality of life and high treatment costs pose significant challenges. Therefore, the urgent need for effective advanced liver cancer treatment strategies is indisputable. Recent advancements in immunotherapy promise a potential revolution in this field. This study aims to comprehensively understand the current landscape and emerging trends in HCC immunotherapy through bibliometric analysis. Method: We performed an extensive literature search from 1999 to 2022, using the Science Citation Index Expanded (SCI-Expanded) database. The strategy yielded 4,486 papers. After excluding self-citations, we analyzed 68,925 references, cited 119,523 times, with an average citation frequency of 26.64 per paper and an h-index of 135. Tools like Citespace and VOSviewer facilitated a detailed evaluation of the literature, with a method encompassing timeline analysis, burst detection, and co-occurrence analysis. Results: Our bibliometric analysis revealed a substantial rise in publications related to HCC immunotherapy during 2021-2022, exceeding the total number of papers published in the preceding decade 2011-2020, highlighting a marked rise in research interest. China, the United States, and Japan were the major contributors. A co-reference network analysis showed a shift in research focus within the field of HCC immunotherapy, underscoring the evolving dynamics. Conclusions: Our bibliometric study highlights the significant evolution and growth in HCC immunotherapy research over the past two decades. Looking ahead, research will focus on improving the microenvironment post-drug resistance from immune combination therapy, harnessing adoptive cellular immunity (as CAR-T), subclassify the population and developing new tumor markers. Incorporation of technologies such as nanotechnology, microbiology, and gene editing will further advance HCC treatments. This progressive trajectory in the field promises a brighter future for individuals suffering from HCC.